A taxonomic discussion of the genus Phalacrotophora Enderlein, 1912 (Diptera: Phoridae), with the description of two new species from Southeast Asia - Lengyel, Gábor Dániel (Zootaxa, 2011)
Two new species of Phalacrotophora Enderlein, 1912, P. nitida sp. n. and P. pappi sp. n. are described from Southeast Asia. Their affinities are discussed, the present knowledge on the genus is summarized. Faunistic records of various Phalacrotophora species are presented; P. fasciata (Fallén, 1823), so far only known from Europe, is reported from Asia for the first time.